Life-threatening massive hemoptysis due to pulmonary arteriovenous malformation: An uncommon case - Nguyen Lan Hieu, PhD; Le Hoan, PhD; Nguyen Ngoc Cuong, PhD; Le Van Tu, MD; Nguyen Thi Giang, MD; Thieu Thi Tra My, MD; Bui Thi Phuong Thao, MD; Tran Quoc Hoa, PhD (Radiology Case Reports, 2025)
We present the case of a 42-year-old woman with no past medical history who was admitted to the emergency department because of massive hemoptysis estimated to be greater than 250ml of fresh blood. Physical examination revealed that her vital signs were initially fluctuating on admission with decreased arterial oxygen saturation, tachypnea, mildly elevated blood pressure and heart rate, and no fever. The head and neck exams were notable for the presence of blood in the oropharynx. No active bleeding site was found during nasopharyngoscopy. Chest X-ray shows a well-defined homogeneous mass-like opacity with lobulated shapes of the right lung. Contrast-enhanced computed tomography demonstrates a single 1.2 × 1 cm pulmonary arteriovenous malformation (PAVM) in the right upper lobe fed by an anterior segment pulmonary artery measuring 3.5mm in diameter. The final diagnosis was concluded as massive hemoptysis due to right pulmonary arteriovenous malformation. In this report, we present a rare clinical case with a silent developmental PAVM that did not cause symptoms until massive hemoptysis which can be life-threatening.